Implementation and Implication of Ignoring Small Polyps at Colonoscopy - Jana G. Hashash; Ibrahim Hanouneh; Swaytha Ganesh; John Nasr; Robert E. Schoen (Archives of Clinical Gastroenterology - Peertechz Publications, 2015)
Background and Aim: CT colonography has promoted a new paradigm, that up-to 2 polyps ≤5mm can be left in-situ and followed. In contrast, endoscopists identify and remove all colorectal polyps, regardless of size. We evaluated whether and how endoscopists might implement a plan of ignoring small polyps in clinical practice. Methods: We prospectively queried endoscopists as they encountered small polyps with a hypothetical question: "If you accepted and believed in a new paradigm that a polyp ≤5mm does not need to be endoscopically removed, would you remove this polyp?" We assessed how the new paradigm would be implemented by gastroenterologists and the pathologic impact of ignoring polyps' ≤5mm. Results: Of 141 patients undergoing colonoscopy, 55 (39%) had polyps and 35 (24.8%) had only small polyps ≤5mm. Endoscopists were agreeable to implementing the new paradigm of not removing small polyps in 17/35 (48.6%) patients. Of patients with only small polyps where endoscopists agreed to forego removal, 13/17 (76.5%) had ≥1 adenomatous polyp. Among the 18/35 subjects for whom the ndoscopists would remove the small polyp because of appearance or clinical situation, 12/18 (66.7%) had ≥1 denoma (p=0.521). If polyps in subjects with only diminutive polyps were ignored, 35/55 (64%) of colonoscopies with therapy would be obviated, at an impact of not removing small adenomas in approximately 75% (25/35). Conclusion: Ignoring polyps' ≤5mm reduces therapeutic colonoscopy at a price of missing a substantial number of small adenomas.